Perception of Studying Mandarin from Home: An Analysis from McLelland’s Theory - Low, Hiang Loon; Goh, Chin Shuang; Teh, Hong Siok; Aini, Tuan Sarifah (Jurnal Arbitrer, 2025)
Studying from home may cause problems for academic performance and psychological well-being, however, studying from home may bring advantages for “flexibility”, “study-life balance” and academic achievement. Hence, this paper investigated whether university students gained benefits by studying Mandarin (as a foreign language) from home based on the Theory of Needs of David McClelland. This theory has linked to the Need for Power (through Flexibility), the Need for Affiliation (through Study-Life Balance) and the Need for Achievement (through Learning Performance). The study employed a quantitative method, and the instrument used was a survey. The samples comprised of 326 students who enrolled in a Mandarin course at the Universiti Teknologi MARA (UiTM), Shah Alam and Puncak Alam, Selangor. The data was analysed using the Statistical Packages for Social Sciences (SPSS) for obtaining descriptive statistics such as mean scores, standard deviations and correlation. In terms of the Need for Power (through Flexibility), the results demonstrated that students very often had the power for saving on commuting expenses and focus on the study; while the results for the Need for Affiliation (through Study-Life Balance) revealed that students were able to save more time to handle tasks on hand, attend to family needs and enhanced family relationship. The results for the Need for Achievement (through Learning Performance) indicated that students very often had control over learning performance due to their Mandarin lecturers understood their challenges, provided more learning materials and monitored their progress. It is recommended that the motivation to study from home can be further explored. This study could be replicated to examine if the McClellan’s Needs Theory would meet the needs of other larger groups of students.